Frequency of Preeclampsia Induced Acute Kidney Injury - Irfan Elahi, Bilal Rasool, Bilal Javaid, Muhammad Anees, Yasir Hussain, Shahbaz Pervaiz (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to ascertain the prevalence of preeclampsia-related acute renal injury among patients who report to a tertiary care facility. Methodology: This Cross-sectional study was conducted at King Edward Medical University and allied hospitals in Department of Nephrology/Mayo hospital Lahore and department of Gynecology, Lady Atchison Hospital Lahore, affiliated with King Edward Medical University. After obtaining the patient’s informed consent, if the patient is able to give it; otherwise, consent was obtained from the attending guardian; the study included all 180 pregnant females with acute kidney disease who were in the third trimester of pregnancy and were presenting for delivery. Patients’ ages ranged from 15 to 50 years. Women who were pregnant and had a blood pressure reading that was greater than 140/90 mmHg after 20 weeks of pregnancy and who had proteinuria on a urine dipstick examination were recorded. This information was taken from a previous record. The laboratory at King Edward Medical University and Mayo hospital in Lahore was where all of the investigations were carried out. Following the establishment of a diagnosis, the patients were then treated in a hospital environment in accordance with the protocols. Results: Patients’ mean ages were 30.21+5.35, their mean blood pressure was 154.27+108.15 mm Hg, their mean serum creatinine was 4.39+0.28 mg/dl, the mean frequency of urine protein was 112.22 percent, and the mean frequency of preeclampsia-induced AKI in pregnancy was 26.11 percent. Conclusion: This research led me to the conclusion that preeclampsia-induced acute kidney damage occurs frequently and must be detected and treated effectively to prevent maternal mortality and morbidity and to improve foetal outcome. A nephrological workup should be performed on women with pre-eclampsia if their proteinuria and hypertension persist longer than 6-8 weeks after delivery. Keywords: Pre-eclampsia, acute kidney injury, frequency